Study guides

Q: Solve the equation by substitution method x-y equals 5?

Write your answer...

Submit

Related questions

You cant solve it unless it is an equation. To be an equation it must have an equals sign.

by elimination,substitution or through the matrix method.

-2

Since the second equation is already solved for "y", you can replace "y" by "9" in the other equation. Then solve the new equation for "x".

That's exactly the purpose of the substitution method ... to get an equation with one less variable. When you have it, you solve it for the variable that's left.

You'd need another equation to sub in

There are no disadvantages. There are three main ways to solve linear equations which are: substitution, graphing, and elimination. The method that is most appropriate can be found by looking at the equation.

what is the solution of x-5y=10 and 2x-10y=20

(2,3)

This is not Calculus.y=7(Already solved)substiute y=7 into y=8xtherefore 7 = 8xtherefore x = 7/8

You can solve lineaar quadratic systems by either the elimination or the substitution methods. You can also solve them using the comparison method. Which method works best depends on which method the person solving them is comfortable with.

z=pq

To solve the following equation by substitution, we need to have the equal sign. This will help us group the knowns and the unknowns.

what does the equation equal? if it equals zero: 0= 3x(4-11) 0=3x(-7) 0=3x 0=x if the equation doesn't equal anything, it means it's just an expression meaning you can't solve for x, you can only reduce (and this equation is already reduced). if the equation equals y, you need another equation and use either substitution or elimination to solve for x.

-3x = 3 + y 3 + y - 5y = -21 -4y = -24 y = 6 x = -3

You solve the two equations simultaneously. There are several ways to do it; one method is to solve the first equation for "x", then replace that in the second equation. This will give you a value for "y". After solving for "y", replace that in any of the two original equations, and solve the remaining equation for "x".You solve the two equations simultaneously. There are several ways to do it; one method is to solve the first equation for "x", then replace that in the second equation. This will give you a value for "y". After solving for "y", replace that in any of the two original equations, and solve the remaining equation for "x".You solve the two equations simultaneously. There are several ways to do it; one method is to solve the first equation for "x", then replace that in the second equation. This will give you a value for "y". After solving for "y", replace that in any of the two original equations, and solve the remaining equation for "x".You solve the two equations simultaneously. There are several ways to do it; one method is to solve the first equation for "x", then replace that in the second equation. This will give you a value for "y". After solving for "y", replace that in any of the two original equations, and solve the remaining equation for "x".

x=1, y=1

You solve one of the equation for one of the variables. For example, if the variables involved are "x" and "y", you might solve for "y". It doesn't really matter what variable you solve for first, so you can solve for whatever variable is easiest to solve. Then - assuming you got, for example, "y = 3x -1", in this example you would replace every "y" by "3x - 1" in the other equation or equations.

y = x - 7 x + y = 5 Substituting for y in the second equation, x + (x - 7) = 5 or 2x = 12 so that x = 6 Then, from the first equation, y = 6 - 7 = -1 So, (x, y) = (6, -1)

It is not an equation if it does not have an equals sign. You could simplify it but not solve it.

You use substitution when you can solve for one variable in terms of the others. By substituting, you remove one variable from the equation, which can then be solved. Once you solve for one variable, you can use substitution to find the other.

a equals 5

From first equation: y = 2x - 5Substitute this in second equation: 3(2x - 5) - x = 5, ie 6x - 15 - x = 5ie 5x = 5 + 15 so x = 4 and y = 3

From first equation, -y = 3x + 3. Substitute in second equation: -3x + 5(3x + 3) = -21 ie 12x = -36 so x = -3 and y = -(-9 + 3) = 6. Easier method: subtract first equation from second giving -4y = -24 so y = 6, this in first equation gives -6 = 3x + 3, ie 3x = -9 so x = -3

G-Given U-Unknown E-Equation S-Substitution S-Solve